Numerical simulation on wind-sand flow field around railway embankment with different wind angles - Zhang, Xian; Xie, Shengbo; Pang, Yingjun (Frontiers in Environmental Science, 2023)
The intersection angles of the railway trend and wind direction are different in practical engineering, resulting in different sand hazard intensities. This research explores the characteristics of the wind-sand flow field, wind speed change, and sand accumulation near railway embankments with different wind angles to reveal the formation mechanism of sand hazards. A numerical simulation of the wind-sand flow field around embankments under wind angles of 15°, 30°, 45°, 60°, 75°, and 90° with different friction wind speeds is conducted on the basis of the Euler two-phase flow model; moreover, the variation law of wind speed and the characteristics of sand accumulation distribution near the railway are discussed. Results indicate that when the wind-sand flow moves to the embankment, it is obstructed and forms different velocity zones. The deceleration zone on both sides of the embankment and the acceleration zone above the embankment increase remarkably with the increase in wind angle. When the friction wind speed is constant, the greater the wind angle, the greater the variation of wind speed near the surface around the embankment, which is more evident on the leeward side of the embankment. The sand accumulation account on both sides increases with the increase in the wind angle. Under a wind angle of 30°, almost no sand accumulated on the leeward side slope. With the increase in friction wind velocity, the sand accumulation account on the windward side of the other embankment decreased except for the embankment with a wind angle of 90°, and that on the leeward side of the other embankments decreased except for the embankment with a wind angle of 15°. These results provide a theoretical basis for the route survey and design of the railways in blown sand areas and the optimization of prevention and control measures.